The Early Screening for Autism and Communication Disorders: Field-testing an autism-specific screening tool for children 12 to 36 months of age. (October 2021) - Wetherby, Amy M; Guthrie, Whitney; Hooker, Jessica L; Delehanty, Abigail; Day, Taylor N; Woods, Juliann; Pierce, Karen; Manwaring, Stacy S; Thurm, Audrey; Ozonoff, Sally; Petkova, Eva; Lord, Catherine
There is a critical need for validated screening tools for autism spectrum disorder in very young children so families can access tailored intervention services as early as possible. Few screeners exist for children between the recommended screening ages of 18–24 months. This study examined the utility of a new autism-specific parent-report screening tool, the Early Screening for Autism and Communication Disorders for children 12–36 months. Field-testing was conducted from five sites with 471 children screened for communication delays in primary care or referred for familial risk or concern for autism spectrum disorder. The Early Screening for Autism and Communication Disorders was evaluated in three age groups: 12–17, 18–23, and 24–36 months. A best-estimate diagnosis of autism spectrum disorder, developmental delay, or typical development was made. Receiver operating characteristic curves were examined for all 46 items and the 30 items that best discriminated autism spectrum disorder from the non-spectrum groups. Area under the curve estimates for the total were greater than 0.90 across age groups. Cutoffs were established for each age group with sensitivity between 0.86 and 0.92 and specificity between 0.74 and 0.85. Results provide preliminary support for the validity of the Early Screening for Autism and Communication Disorders as an autism-specific screener in children 12–36 months with elevated risk of communication delay or autism spectrum disorder. Lay abstract: There is a critical need for accurate screening tools for autism spectrum disorder in very young children so families can access tailored intervention services as early as possible. However, there are few screeners designed for children 18–24 months. Developing screeners that pick up on the signs of autism spectrum disorder in very young children has proved even more challenging. In this study, we examined a new autism-specific parent-report screening tool, the Early Screening for Autism and Communication Disorders for children between 12 and 36 months of age. Field-testing was done in five sites with 471 children screened for communication delays in primary care or referred for familial risk or concern for autism spectrum disorder. The Early Screening for Autism and Communication Disorders was tested in three age groups: 12–17, 18–23, and 24–36 months. A best-estimate diagnosis of autism spectrum disorder, developmental delay, or typical development was made. Analyses examined all 46 items and identified 30 items that best discriminated autism spectrum disorder from the non-spectrum groups. Cutoffs were established for each age group with good sensitivity and specificity. Results provide preliminary support for the accuracy of the Early Screening for Autism and Communication Disorders as an autism-specific screener in children 12–36 months with elevated risk of communication delay or autism spectrum disorder.